1980
DOI: 10.1073/pnas.77.1.670
|View full text |Cite
|
Sign up to set email alerts
|

Autoradiographic localization of gamma-aminobutyric acid (GABA) receptors in the rat cerebellum.

Abstract: [3H]Muscimol was used in the light microscopic autoradiographic localization of 7-amninobutyrip acid (GABA) receptors in the rat cerebellum. The binding ofI3Hl muscimol to the slide-mounted tissue sections had all of the characteristics associated with a GABA receptor. It was saturable with appropriate kinetic constants and was blocked only by other GABAergic drugs. Autoradiographic studies revealed a very high density of receptors over the granule cell layer, a low level over'the molecular layer, and negligib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

1981
1981
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(35 citation statements)
references
References 28 publications
3
32
0
Order By: Relevance
“…The only exception was the Kd of muscimol, which was found to be 0.7-5.5 nM in our study, comparing reasonably well with �13 nM in whole brain sec tions in one study (Palacios et al, 1980), but not with 35-59 nM in two other studies (Penney et al, 1981;Pan et al, 1983). This discrepancy may be related to differences in technique; since muscimol binds to both the low-and high-affinity forms of the GABAA receptor, the conditions of the assay, es pecially the rinse time, can affect which form is predominantly reflected by the binding.…”
Section: Regional Kinetics Of Bindingsupporting
confidence: 88%
“…The only exception was the Kd of muscimol, which was found to be 0.7-5.5 nM in our study, comparing reasonably well with �13 nM in whole brain sec tions in one study (Palacios et al, 1980), but not with 35-59 nM in two other studies (Penney et al, 1981;Pan et al, 1983). This discrepancy may be related to differences in technique; since muscimol binds to both the low-and high-affinity forms of the GABAA receptor, the conditions of the assay, es pecially the rinse time, can affect which form is predominantly reflected by the binding.…”
Section: Regional Kinetics Of Bindingsupporting
confidence: 88%
“…Benzodiazepine receptor localization in the molecular layer of the cerebellar cortex (where the dendritic arborizations of the Purkinje cells reside) supports this hypothesis. Studies with human cerebellum demonstrated the same distribution of GABA receptors described here (18). However, while the rat cerebellum did not show any significant labeling of benzodiazepine receptors in the granule cell layer, the human cerebellum demonstrated equal concentrations of benzodiazepine receptors in the molecular layer and granule cell layer (34).…”
Section: Discussionmentioning
confidence: 70%
“…In cerebellum the period of the largest in crease in the number of receptor sites coin cides with the development of the granule cells [34], in agreement with the suggestion by Simantov et al [38] and Olsen and Mikoshiba [31] that a major fraction of the GABA receptors in cerebellum resides on this cell type. Moreover, this is in line with autoradio graphic studies of GABA binding to cerebel lar slices [33] and cerebellar cultures [14][15][16] as well as with the finding that muscimol binding is enriched in cerebellar glomeruli [17]Although GABA or muscimol binding has been studied in cultured neurons from cere brum or spinal cord [7,8,15,39,41], no such studies have been performed on cerebellar cultures. Since it appears that granule cells possess a large fraction of the cerebellar GABA receptors and since this cell type can be cultured relatively easily [28] we decided to study GABA binding to such cells in cul ture.…”
Section: Introductionmentioning
confidence: 78%